1993
DOI: 10.1073/pnas.90.3.893
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic amphipathic peptide-DNA complexes mediate high-efficiency transfection of adherent mammalian cells.

Abstract: A DNA transfection protocol has been developed that makes use of the cyclic cationic amphipathic pepffde gramicidin S and dioleoyl phosphatidylethanolamine. The DNA complex is formed by mixing gramicidin S with DNA at a 1:1 charge ratio and then adding phosphatidylethanolamine at a lipid/peptide molar ratio of 5:1. The complex mediates rapid association of DNA with cells and leads to transient expression levels of -galactosidase ranging from 1 to 30% of the transfected cells, with long-term expression being ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 20 publications
1
46
0
Order By: Relevance
“…In contrast, another cyclic amphipathic peptide, gramicidin S, also condenses DNA, and, when combined with a DNA/DOPE complex, enables gene transfer by an apparently pH independent mechanism. 139 While JTS-1, KALA, and gramicidin S all apparently enhance gene transfer, presumably by inducing endosomolysis, it remains unclear as to whether these peptides form pores or disrupt membranes via mechanisms similar to GALA and melittin. Pore formation by both GALA and melittin peptides, on the other hand, may accelerate an additional mechanism of membrane penetration by phospholipid 'flip-flop', as described next.…”
Section: Endosomolysismentioning
confidence: 99%
“…In contrast, another cyclic amphipathic peptide, gramicidin S, also condenses DNA, and, when combined with a DNA/DOPE complex, enables gene transfer by an apparently pH independent mechanism. 139 While JTS-1, KALA, and gramicidin S all apparently enhance gene transfer, presumably by inducing endosomolysis, it remains unclear as to whether these peptides form pores or disrupt membranes via mechanisms similar to GALA and melittin. Pore formation by both GALA and melittin peptides, on the other hand, may accelerate an additional mechanism of membrane penetration by phospholipid 'flip-flop', as described next.…”
Section: Endosomolysismentioning
confidence: 99%
“…We should note that the results in Figures 1 and 2 may be directly compared since they were obtained with the same batch of cells. Several studies have found that DOPE is the most efficient helper lipid for in vitro gene transfection, 31,44,45 most likely because of its tendency to form nonbilayer phases and to facilitate membrane fusion. 46,47 Our results with the control liposomes, ie in the absence of transferrin (Figures 1 and 2), also indicate that DOTAP:DOPE liposomes mediated higher transfection activity than pure DOTAP liposomes.…”
Section: Enhancement Of Transfection Of Hela Cells By a Targeting Ligandmentioning
confidence: 99%
“…44,51,52 To test whether DOTAP:DOPE/DNA complexes associated with transferrin or GALA were also effective in other cell lines we performed experiments with COS-7 cells which have been used in previous transfection studies ( Figure 4). 51 As observed for HeLa cells, the association of transferrin or the GALA peptide with the lipid/DNA complexes resulted in a significant enhancement of the levels of luciferase expression in COS-7 cells.…”
Section: Enhancement Of Transfection Of Hela Cells By a Targeting Ligandmentioning
confidence: 99%
“…10,11 However, these systems often require a large amount of peptides per pDNA complex in order to be effective, partially explaining their limited reports of successes in vivo. 12 Viruses are not the only species that evolved and refined the ability to carry their genomic contents across the membrane barrier of host cells.…”
Section: Introductionmentioning
confidence: 99%